Η προΰπαρξη του Ιησού στο κατά Μάρκον Ευαγγέλιο υπό παλαιοδιαθηκικό πρίσμα - Χρήστος Καρακόλης (Βιβλικές μεταφράσεις: Ιστορία και Πράξη. Επετειακός επιστημονικός τόμος για τα διακόσια χρόνια της Ελληνικής Βιβλικής Εταιρίας, 2021)
Abstract CHRISTOS KARAKOLIS: The Preexistence of Jesus in Mark’s Gospel from an Old Testament Perspective Despite the fact that the Gospel of Mark does not clearly refer to the pre-existence of Jesus Christ, there are significant indications that it is both implied and presupposed. Among the various theories relevant to this issue one can discern the interpretation of Mark 1:2-3 as a passage referring to a heavenly dialogue between God and His Son prior to the beginning of John the Baptist’s preaching in the world, the preaching that will prepare the course of the Son of God in the world. Following the interpretation of Mark 1:1-3 a translational deficit is highlighted that comes from the non-clarification of the identity of these two heavenly discussants. Although, some translations highlight the fact that in v.2 the conversing subject is indeed God, there is no translation that names the other conversant. This is, indeed, a necessary aspect that should be presented in a dynamic translation so that the reader will be able to un- derstand from the onset the Christological teaching of the Gospel of Mark.